Reaction of the Geomagnetic Field on the Earthquakes Preparation Process in Georgia - Jimsheladze, Tamar T.; Melikadze, George G.; Kobzev, Genadi N.; Tchankvetadze, Aleksandre Sh.; Matiashvili, Tamaz G. (Journals of Georgian Geophysical Society, 2024)
During the monitoring of earthquake precursors including extra information as the variations of electromagnetic fields analysis, it is possible to define earthquakes precursors is very actual and important problem. Connection between the variation of the geomagnetic field and seismic activities is an essential element of the fundamental problem of earthquake forecasting. In terms of geodynamic, Georgia is one of the most active regions. The macro structural factor here is represented by the contact with the Arabian and Eurasian tectonic plates, which in addition to the geological diversity of the area conditions the high seismicity of mentioned region. The article represents the observations of following seismic processes such as: geomagnetic field.